Bioanalytical and validation high-performance liquid chromatography method for simultaneous quantification cefotaxime and ciprofloxacin in human plasma - Luh Putu Mirah Kusuma Dewi, Djoko Wahyono, Ika Puspitasari, Rizka Humardewayanti, Endang Lukitaningsih (Journal of Applied Pharmaceutical Science, 2024)
This study aims to obtain a validated method for simultaneously determining cefotaxime and ciprofloxacin levels in spiked human plasma. The chromatographic system used a Luna Phenomenex® C18 column (250 × 4 mm i.d; 5 μm), and a mobile phase consisting of an isocratic mixture of 0.02 M phosphate buffer (pH 3.0), acetonitrile (ACN), and methanol (80:12:8 v/v), flow rate 1.0 ml/minute, 280 nm. Extraction of human plasma was carried out using 100 μl of acetic acid 10% and ACN, and extraction was repeated twice, the supernatant obtained was collected and then evaporated to dryness. The dried sample was dissolved with 500 μl of mobile phase before being injected into the system. The method was validated by evaluating the selectivity, linearity, accuracy, precision, and stability parameters. This method was declared valid for the simultaneous determination of cefotaxime and ciprofloxacin levels in human plasma and it is stated to be linear with the value of the correlation coefficient of 0.9986 for cefotaxime and 0.9981 for ciprofloxacin. The average percent recovery of cefotaxime was in the range of 89.13 and 112.81. Meanwhile, ciprofloxacin was in the range of 94.33 and 107.98. The developed analytical method is stated to fulfill the validity requirements.
Keywords: Cefotaxime, ciprofloxacin, HPLC, validation, plasma